Religious Coping and Psychological Distress in Military Veteran Cancer Survivors - Trevino, Kelly M. (Journal of religion and health, 2012)
Research on the relationship between religious coping and psychological well-being in cancer survivors is limited. Forty-eight veteran cancer survivors completed measures of psychological distress, posttraumatic growth, and positive and negative religious coping. Negative religious coping was associated with greater distress and growth. Positive religious coping was associated with greater growth. Gender, race, and religious affiliation were significant predictors of positive and negative religious coping. Veteran cancer survivors who utilize negative religious coping may benefit from referral to clergy or a mental health professional. Assessment of religious coping may be particularly important for female, non-White, and Christian cancer survivors.